Frequency of Pulmonary Hypertension among Twice Weekly Maintenance Haemodialysis Patients: A Single Centre Study (Community Based Medical Journal, 2026)
Pulmonary hypertension (PH) is a recognized complication of chronic kidney disease (CKD), particularly in end-stage renal disease, with prevalence estimates ranging from 30% to 50%. It is an independent predictor of increased mortality in this patient population. A cross-sectional observational study was conducted at the National Institute of Kidney Diseases & Urology (NIKDU), Dhaka, Bangladesh, from December 2022 to March 2023, to determine the frequency of pulmonary hypertension among patients on a twice-weekly maintenance hemodialysis regimen. We adopted convenient purposive sampling technique. A total of 81 hemodialysis patients were enrolled. Data was collected through a pre-tested questionnaire including patients’ history, clinical examination, laboratory findings, and other medical records review. The prevalence of pulmonary hypertension was 25(30.9%). No significant association was observed between pulmonary hypertension and duration of hemodialysis (29.8±24.3 months) or ultrafiltration volume (2.80±0.53 L). Cardiac abnormalities were prevalent, including regional wall motion abnormalities in 45.7% of patients. Pulmonary hypertension was highly prevalent in patients having twice-weekly hemodialysis and is significantly associated cardiac morbidity. Its development appears independent of dialysis vintage or ultrafiltration volume.  CBMJ 2026 January: vol. 15 no. 01 P:168-173